Mechanism of Efficient Smithsonite Flotation with a Ternary Composite Collector Under Sulfur-Free Conditions - Rui Li; Yanhai Shao; Jinhui Li; Chenjie Liu; Hongqin Chen; Xiao Meng; Xinru Jia (Molecules)
The increasing demand for zinc resources and the declining availability of sulfide zinc ore reserves have made the efficient utilization of zinc oxide a topic of considerable interest. In this study, a ternary composite collector ABN (Al-BHA-NaOL system) was applied to the direct flotation of smithsonite. Micro-flotation studies showed that at pH 9, ABN exhibited better adsorption on smithsonite, achieving a recovery rate of 80.62%. Visual MINTEQ 3.1 and zeta potential analysis confirmed that ABN predominantly reacted with Zn(OH)2(aq) on the surface of smithsonite. Furthermore, X-ray photoelectron spectroscopy (XPS) analysis results elucidated the formation of Al-O bonds through chemical adsorption on the smithsonite surface. Additionally, powder contact angle measurements indicated that ABN enhances the surface contact angle of smithsonite. These results illuminate that ABN is adsorbed by reacting with O sites on hydroxylated metal ions on the smithsonite surface, with Al serving as the adsorption center, thereby achieving separation and purification. Due to ABN’s adsorption characteristics, smithsonite can achieve efficient and clean direct flotation recovery without sulfidization.